Bacterial repopulation of drinking water pipe walls after chlorination. Issue 8 (13th September 2016) - Mathieu, Laurence; Francius, Grégory; El Zein, Racha; Angel, Edith; Block, Jean-Claude
Abstract: The short-term kinetics of bacterial repopulation were evaluated after chlorination of high-density polyethylene (HDPE) colonized with drinking water biofilms and compared with bare HDPE surfaces. The effect of chlorination was partial as a residual biofilm persisted and was time-limited as repopulation occurred immediately after water resupply. The total number of bacteria reached the same levels on both the bare and chlorinated biofilm-fouled HDPE after a seven-day exposure to drinking water. Due to the presence of a residual biofilm, the hydrophobicity of chlorinated biofilm-fouled surface exhibited much lower adhesion forces (2.1 nN) compared to bare surfaces (8.9 nN). This could explain the rapid repopulation after chlorination, with a twofold faster bacterial accumulation rate on the bare HDPE surface. γ-Proteobacteria dominated the early stages of repopulation of both surfaces and a shift in the dominance occurred over the colonization time. Such observations define a timescale for cleaning frequency in industrial environments and guidelines for a rinsing procedure using drinking water.